Model of Strengthening Governance of Education Fees in Madrasah - Karim, Rhafiiqul Azhari; Karim, Hamdi Abdul (Jurnal Inovatif Manajemen Pendidikan Islam, 2025)
The high challenge of transparency and efficiency in the management of education funds in madrasas encourages the need to develop a model to strengthen accountable, participatory, and sustainable education cost governance to ensure access to quality and equitable education. This study aims to design a model to strengthen contextual and applicable education cost governance in Madrasah Ibtidaiyah Swasta (MIS) Piladang, Fifty Cities Regency. This study uses a descriptive qualitative approach with a case study method, where data is collected through interviews, and participatory observation. The results of the study show that the financial management system at MIS Piladang still faces a number of challenges, such as delays in disbursing funds, arrears of education infaq, and limitations of the financial digitalization system. However, there are positive initiatives in the form of the involvement of the madrasah committee, as well as the preparation of Madrasah Activity Plans and Budgets (RKAM) based on real needs. The proposed governance strengthening model includes the application of good governance principles, digitization of financial management, community-based supervision, and cross-stakeholder collaboration. This model is expected to be able to improve the efficiency, transparency, and accountability of education cost governance, while supporting the achievement of a more equitable and equitable quality of education.